A 16,000 year multiproxy record from lake Holzmaar (Germany): diatom and geochemical stratigraphies - María Luján García; Stella Birlo; Bernd Zolitschka (PANGAEA, 2022)
Lacustrine environmental archives with annually laminated (varved) sediments permit a calendar-year chronology and allow calculation of precise sediment accumulation rates. We present multiproxy analyses of a varved sediment record from Holzmaar (West-Eifel Volcanic Field, Germany) for the last 16,000 years providing a continuous diatom stratigraphy supported by physical and chemical parameters with a centennial resolution. Patterns of diatom assemblages infer the trophic history of Holzmaar. There is a distinct variation at the Pleistocene/Lateglacial transition characterized by a replacement of Staurosira construens with Stephanodiscus minutulus, increases of Ca/Ti, TOC/TN ratios and biogenic silica, together suggesting an increase in lacustrine productivity and a shift of the lake extquotesingles trophic status from oligotrophic to mesotrophic. These conditions remain during the Bölling/Alleröd interstadial. During the Younger Dryas stadial, there is a decrease on organic productivity as reflected by TOC, a subtle increase on benthic and epiphytic diatoms, indicating colder and dry conditions, and S. minutulus remains dominant suggesting increased winds. The Postglacial is dominated by Lindavia radiosa, S. minutulus and Nitzschia paleacea. The latter occurs between 9000-6000 cal yr BP together with an increase of TOC/TN and TS suggesting eutrophication with periodic anoxia during the Holocene Thermal Maximum. After 2200 cal yr BP, L. radiosa and Pantocsekiella comensis are dominant suggesting warmer conditions (especially during the Medieval Climate Anomaly) and thermal stability. Increased surface runoff is reflected in higher values of Ti and MS, suggesting more humidity and enhanced by anthropogenic disturbance. Moreover, the appearance of Aulacoseira subarctica is related to a cold and wet period coinciding with the Little Ice Age. In addition to environmental changes, our multiproxy analyses track human impact since the Middle Neolithic.